Methodology for distribution centers location through multicriteria analysis and optimization (2014)
This paper presents a combined methodology based on multicriteria decision analysis and optimization for the distribution centers location problem. The initial approach consists of a set of relevant quantitative and qualitative attributes used for the decision of locating distribution centers. From quantitative criteria a multi-objective mathematical programming model to minimize costs is proposed. This model provides alternative solutions that may be compared to the other ones initially known. These solutions are assessed for a multicriteria decision model which incorporates qualitative considerations of the problem that are infeasible to represent algebraically. Therefore, the application of the multi-criteria decision analysis model evaluates a set of feasible solutions to suggest for the best alternative considering several attributes.